Legalitas Praktik Siber yang Licik: Kesiapan Hukum Siber Indonesia: The Legality of Devious Cyber Practices: Readiness of Indonesia's Cyber Laws - Sardjana Orba Manullang (Society, 2022)
The ever-expanding Indonesian cyberspace has ushered in significant economic growth to the country’s online business and e-commerce. This is due to the country’s rising internet penetration rate of 73% of its total population, with about 204 million people connected to the internet. This high connectivity has brought about several positive socio-economic opportunities but with other thorny issues like cybercrime, misinformation, cyber-induced intolerance, disinformation, trolling and cyber warfare. Despite the Indonesian government’s intervention with measures to regulate cyber activities, some devious cyber practices undefined in legal literature continue to be practiced, even passed as legitimate, sometimes leading to negative consequences. These practices are often conducted as organized operations that target populations to create mistrust and polarize the targeted population. Some are crafted as cyber warfare declared by entities within a country or from a foreign country targeting another’s populace, which poses a threat to social order. This paper explores these devious cyber practices and their strategies and mitigation possibilities. A sociological research approach coupled with the use of law enforcement theory was applied to study and analyze Indonesia’s cyber security law enforcement policies, the Internet and Electronic Transaction (ITE) Law, the Criminal Prosecution Act, the Constitutional law, civil society actors and private sector actors on cyber security. Indonesian law and international law, coupled with available technology, were reviewed for readiness to address threats posed by these devious cyber issues to social order. Measures taken by the Indonesian government are in readiness to combat these cyberspace issues in its jurisdiction but also present more questions on the proposals for reviews to the legislation and introduction of content monitoring systems, which risk being inappropriately deployed in censorships or suppression of legitimate freedom of expression.